Circulating Galectin-3 Levels Associated with Insulin Resistance in Gestational Diabetes Mellitus: A Cross-sectional Study - Lakshmi Vijukumar; P Renuka; VM Vinodhini; Karthiga J Prabhu; Ashish Kumar; Aryan Kumar Singh (Journal of Clinical and Diagnostic Research)
Introduction: Gestational Diabetes Mellitus (GDM) is a prevalent pregnancy complication with significant health implications for both the mother and offspring. Galectin-3, a protein expressed in various cells, contributes to cellular and systemic insulin resistance and is secreted into extracellular fluid. However, the link between Galectin-3 and insulin resistance in the development of GDM has not been firmly established. Aim: To estimate the circulating Galectin-3 levels in diagnosed GDM patients and compare them with those of healthy pregnant women. Materials and Methods: This cross-sectional study was conducted in the Obstetrics and Gynaecology Outpatient Department (OPD) at SRM Medical College Hospital and Research Centre, SRM Institue of Science and Technology, Kattankulathur, Chengalpattu, Tamil Nadu, India, from July 2023 to December 2023, including 40 pregnant women aged ≥18 years in each group. The parameters measured between both groups included the diabetic profile, lipid profile and Galectin-3 levels. The case group consisted of individuals diagnosed with GDM whose Oral Glucose Challenge Test (OGCT) value was ≥140 mg/dL, whereas the control group comprised pregnant women with OGCT values below 140 mg/dL {selected using Diabetes in Pregnancy Study Group of India (DIPSI) criteria}. Independent t-tests, Mann-Whitney U tests and Pearson Correlation were performed using Statistical Package for the Social Sciences (SPSS) (27.0). Results: The mean age of the patients was 27.78±3.84 years in the GDM group and 26.88±3.89 years in the normal pregnancy group. The mean Galectin-3 levels were higher in GDM patients compared to normal pregnant women (4.84±0.75 ng/mL vs. 3.34±0.78 ng/mL; p<0.001). Additionally, GDM patients exhibited significant increases in Fasting Plasma Glucose (FPG), fasting insulin, Homeostatic Model Assessment for Insulin Resistance (HOMA-IR), Triglycerides (TyG) index and Glycated Haemoglobin (HbA1c) compared to normal pregnant women. Conclusion: The present study confirmed the presence of insulin resistance and elevated Galectin-3 levels in pregnancies affected by GDM but did not find a correlation between them.